Methodology for measuring the level of collaboration in a supply chain by making surveys (2017)
Faced with uncertain environments, companies have strived to achieve greater collaboration in the supply chain, achieve alignment of actions, objectives, decisions and sharing of information. The objective of the study is to measure the level of collaboration in the supply chain by making use of a survey and designing a generic process for carrying out the measurement in any company, through a reliable and valid instrument for this construction. The data were collected through a survey of clients of the company chosen for research. Statistical methods used include reliability analysis and AHP analysis for obtaining and verifying results. The results show a medium-low level of collaboration in the supply chain of the company towards its customers and a collaboration efficiency of 69%. There were no significant differences in the scores on the level of collaboration of the different indicators, due to the versatile characteristics of the companies, such as: Size, market and differences of charge between the people surveyed.